Changing demand for livestock food products: An evidence from Indian households - CHENGAPPA, P G; UMANATH, M; VIJAYASARATHY, K; BABU, PRADEEPA; MANJUNATHA, A V (The Indian Journal of Animal Sciences, 2016)
Evidence was established for changing consumption trends towards livestock products making use of the consumer expenditure survey data pertaining to the periods, 2004–05 and 2011–12. The large database of National Sample Survey Organisation was used for estimation of income and demand elasticities through the Quadratic Almost Ideal Demand System (QUAIDS). The results provided useful insights into the increasing domestic demand for livestock products in Indian households. The estimated expenditure elasticities for livestock products such as milk and milk products, chicken, fish and prawn were positive and significant in both rural and urban India. This implied that as the per capita income of the households increased, the proportion of expenditure on these products were much higher than other livestock products. Furthermore, own price elasticities for most of the livestock products, except egg and mutton, were highly elastic indicating the price sensitiveness of demand for these food products among the Indian households.